Freestanding reduced graphene oxide–sulfur composite films for highly stable lithium–sulfur batteries. Issue 14 (22nd March 2017) - Luo, Shuwen; Yao, Minjie; Lei, Song; Yan, Pengze; Wei, Xiang; Wang, Xiaotong; Liu, Lili; Niu, Zhiqiang
Abstract : Freestanding reduced graphene oxide–sulfur (rGO–S) composite films were fabricated by combining solution infiltration of sulfur into solvated rGO films with freeze-drying. Abstract : Freestanding reduced graphene oxide–sulfur (rGO–S) composite films were fabricated by combining solution infiltration of sulfur into solvated rGO films with freeze-drying. Such rGO–S composite films can directly serve as the cathodes of lithium–sulfur (Li–S) batteries. The nanostructured architecture of rGO–S composite films considerably improved the cycling stability of Li–S batteries.